Acute toxicity test of CuO nanoparticles using human mesenchymal stem cells. (October 2014) - Mancuso, Luisa; Cao, Giacomo
Abstract Despite the growing interest in nanoparticles (NPs), standardized procedures for the evaluation of their toxicity have not been defined. The risk of human exposure is rapidly increasing and reliable toxicity test systems are urgently needed. In vitro methods are ideal in toxicology research because they can rapidly provide reproducible results while preventing the use of animals. Recently, a new test for acute toxicity based on the use of human bone marrow mesenchymal stem cells (hBMMSCs) has been developed and successfully tested in our laboratory following the Interagency Coordinating Committee on the Validation of Alternative Methods guidelines. Along these lines, the aim of this study is to evaluate the acute cytotoxicity of copper oxide (CuO) NPs using the new toxicity test based on hBMMSCs. Our results show that CuO NPs are much more toxic compared to micrometer ones. Specifically, CuO NP exposure exhibits a significant cytotoxicity at all the concentrations used, with an IC50 value of 2.5 ± 0.53 µg/ml. On the other hand, CuO microsized particle exposure exhibits a very low cytotoxicity at the same concentrations, with an IC50 value of 72.13 ± 16.2 µg/ml.